MUI Attitude in Maintaining Ukhuwah Ahead of the 2024 Election - Asep Gunawan; Farrah Nurus Syifa; Rega Priandanagari Gevisa (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Elections every year inevitably bring up certain camps that differ in opinion, and the factor of the dispute can divide the Indonesian nation itself, therefore the Indonesian Ulema Council as a government agency needs to strive to always maintain ukhuwah during these election times so that later these camps will not have a bad impact on this country. This journal aims to find out about the attitude of the Indonesian Ulema Council in Maintaining Ukhuwah ahead of the 2024 election. This research uses descriptive qualitative, primary and secondary data. The secondary data used by the author is news spread in online media such as CNN.Com, Kompas.com, and others. While the secondary data are all materials or writings about the things the author examines such as journals, books and others. The results of this study are the attitudes that MUI appealed to the Indonesian people not to criticize each other, so as not to cause a commotion or even the division itself, and always maintain the relationship between one another.